Posttranslational Modifications of Ribosomal Proteins in Escherichia coli - Nesterchuk, M.V. (A.I. Gordeyev, 2011)
А number of ribosomal proteins inEscherichia coliundergo posttranslational modifications. Six ribosomal proteins are methylated (S11, L3, L11, L7/L12, L16, and L33), three proteins are acetylated (S5, S18, and L7), and protein S12 is methylthiolated. Extra amino acid residues are added to protein S6. С-terminal amino acid residues are partially removed from protein L31. The functional significance of these modifications has remained unclear. These modifications are not vital to the cells, and it is likely that they have regulatory functions. This paper reviews all the known posttranslational modifications of ribosomal proteins inEscherichia coli. Certain enzymes responsible for the modifications and mechanisms of enzymatic reactions are also discussed.